SiSTL1, encoding a large subunit of ribonucleotide reductase, is crucial for plant growth, chloroplast biogenesis, and cell cycle progression in Setaria italica - Tang, Chanjuan (Journal of experimental botany, 2019)
© The Author(s) 2018. Published by Oxford University Press on behalf of the Society for Experimental Biology.